Sodium ion battery capable of improving energy density
By using sodium titanate and hard carbon as negative electrode materials in sodium ion batteries and combining P2 phase materials as positive electrode materials, the problem of unknown sodium storage mechanism and unstable process in sodium ion batteries is solved, and the battery energy is improved Density and cycle stability achieve higher charge and discharge performance and safety.
Patent Information
- Application Number
- CN202411617984.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-13
- Publication Date
- 2025-01-14
AI Technical Summary
As the negative electrode material, hard carbon in sodium ion batteries has unknown sodium storage mechanism and unstable process, resulting in low first charge and discharge efficiency and capacity attenuation, affecting the energy density of the battery.
Sodium titanate and hard carbon are used as the negative electrode active material, and P2 phase material is used as the positive electrode active material, so as to improve the energy density and cycle stability of the battery by adjusting the material ratio and component ratio.
It improves the energy density and cycle stability of the battery, reduces the negative electrode working voltage, enhances the charging and discharging performance and safety of the battery, and simplifies the battery design and manufacturing process.
Smart Images

Figure BDA0005132759770000091
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of batteries, and in particular to a sodium ion battery with improved energy density. Background Art
[0002] Sodium-ion batteries have a greater cost advantage than lithium-ion batteries due to their abundant sodium resources. They have good development prospects and are receiving more and more attention. At present, the negative electrode of sodium-ion batteries is basically hard carbon. There are indeed some challenges in using hard carbon as the negative electrode material of sodium-ion batteries, especially because the sodium storage mechanism of hard carbon is unclear and the process synthesis method is also unstable. The surface defects and oxygen-containing functional groups of hard carbon materials may react irreversibly with the electrolyte during the first charge and discharge process, resulting in a decrease in the first coulombic efficiency and capacity decay, which in turn affects the energy density of the battery. Summary of the invention
[0003] The main purpose of the present invention is to provide a sodium ion battery with improved energy density, aiming to improve the energy density of the battery.
[0004] To achieve the above-mentioned object, the sodium ion battery with improved energy density proposed in the present invention comprises a positive electrode sheet and a negative electrode sheet, wherein the positive electrode sheet comprises a positive electrode current collector and a positive electrode coating provided on at least one side of the positive electrode current collector, wherein the positive electrode coating comprises a positive electrode active material, and the positive electrode active material comprises a P2 phase material;
[0005] The negative electrode sheet includes a negative electrode current collector and a negative electrode coating disposed on at least one side of the negative electrode current collector. The negative electrode coating includes a negative electrode active material. The negative electrode active material includes sodium titanate and hard carbon.
[0006] The negative electrode active material of the present application includes sodium titanate and hard carbon, and the positive electrode active material includes a P2 phase material. The combination of the positive electrode active material and the negative electrode active material helps to improve the energy density of the battery.
[0007] It is understandable that sodium titanate (Na2TiO3) has good stability due to its simple crystal structure. Mixing sodium titanate with hard carbon can improve the stability of the negative electrode and provide as a sodium source at the same time, thereby improving energy density. In addition, sodium titanate is simple to synthesize, the process is stable, and the material is relatively cheap. Considering that sodium titanate is used as a negative electrode, its sodium potential is high. By mixing sodium titanate with hard carbon, its sodium potential can be averaged, and P2 phase material is used as the positive active material of the sodium ion battery. This combination of positive and negative electrode systems helps to improve the energy density of the battery. In addition, sodium titanate contains sodium ions, which can achieve the effect of supplementing sodium at the negative electrode. The positive and negative electrode systems of this application can improve the energy density of the battery.
[0008] Optionally, the mass ratio of the sodium titanate to the hard carbon is (3-7): (7-3).
[0009] The mass ratio of sodium titanate to hard carbon satisfies the above range, which helps to improve the energy density of the battery and the cycle stability of the negative electrode.
[0010] Optionally, the P2 phase material includes sodium nickel manganate and / or sodium nickel iron manganate.
[0011] It is understandable that the potential of the positive and negative electrode materials has a direct impact on the energy density of the battery. The energy density of the battery can be estimated by the formula E = (Q × ΔU) / m, where E is the energy density of the battery, Q is the capacity of the battery, ΔU is the average voltage difference between the positive and negative electrodes, and m is the mass of the battery. From this formula, it can be seen that increasing the battery operating voltage (ΔU) can effectively increase the energy density of the battery.
[0012] The layered oxide positive electrode active material of the P2 phase generally exhibits a higher operating voltage and good electrochemical performance, and the negative electrode active material includes a mixture of sodium titanate and hard carbon, which can improve the stability of the negative electrode while reducing the operating voltage of the negative electrode. The use of the positive and negative electrode system of the present application helps to increase the battery operating voltage (ΔU), thereby helping to increase the energy density of the battery.
[0013] For example, in one embodiment, the P2 phase material includes sodium nickel manganese oxide Na 0.72 Ni 0.28 Mn 0.72 O2, in which the molar ratio of sodium (Na) is less than 1, and it is a sodium-deficient material. The negative electrode active material includes sodium titanate, which helps to supplement the sodium on the positive electrode side.
[0014] Optionally, the ratio of the negative electrode capacity to the positive electrode capacity of the sodium ion battery is 0.9 to 1.1, preferably 1:1.
[0015] Using the positive and negative electrode system of the present application, the ratio of the negative electrode capacity to the positive electrode capacity of the sodium ion battery is 0.9 to 1.1, preferably 1:1. The equal positive and negative electrode capacities help balance the redox reactions of the battery, thereby obtaining better charge and discharge performance and cycle stability. When the positive and negative electrode capacities are matched, the sodium storage capacity of the two-pole materials can be fully utilized to improve the energy density of the battery. Matching positive and negative electrode capacities helps reduce irreversible capacity losses during initial charging and improves the coulombic efficiency of the battery. Equal positive and negative electrode capacities can simplify the battery design and manufacturing process because there is no need to consider how to balance the capacities of the two poles. Balanced positive and negative electrode capacities help avoid overcharging or over-discharging due to capacity mismatch, thereby improving the safety of the battery.
[0016] Optionally, the positive electrode coating further comprises a positive electrode conductor and a positive electrode binder, and the mass ratio of the positive electrode active material, the positive electrode conductor and the positive electrode binder is (90-98): (2-8): (2-5);
[0017] And / or, the negative electrode coating further comprises a negative electrode conductive agent and a negative electrode binder, and the mass ratio of the negative electrode active material, the negative electrode conductive agent, and the negative electrode binder is (90-98): (5-8): (2-5);
[0018] And / or, the compaction density of the negative electrode coating is 0.95 g / cm 3 Up to 2.5g / cm 3 ;
[0019] And / or, the mass energy density of the sodium ion battery is 90wh / kg to 145wh / kg.
[0020] The positive electrode coating also includes a positive electrode conductive agent and a positive electrode binder. The mass ratio of the positive electrode active material, the positive electrode conductive agent, and the positive electrode binder is (90-98): (2-8): (2-5). For example, the mass ratio of the positive electrode active material, the positive electrode conductive agent, and the positive electrode binder can be 95:2.5:2.5, etc. The mass ratio of the above components is within the above range, which can ensure the performance of the positive electrode. Among them, the positive electrode active material, the positive electrode conductive agent, and the positive electrode binder can all be the positive electrode active material, positive electrode conductive agent, and positive electrode binder known in the art for sodium ion batteries.
[0021] The negative electrode coating also includes a negative electrode conductor and a negative electrode binder. The mass ratio of the negative electrode active material, the negative electrode conductor, and the negative electrode binder is (90-98): (5-8): (2-5). The mass ratio of the above components is within the above range, which can ensure the performance of the negative electrode.
[0022] The negative electrode active material of the present application includes sodium titanate and hard carbon. The use of the above negative electrode active material can improve the compaction density of the negative electrode coating, which is beneficial to improving the energy density of the battery.
[0023] The energy density of the sodium ion battery using the positive and negative electrode system of the present application is improved.
[0024] Optionally, the negative electrode coating further comprises carbon black, styrene-butadiene rubber and carboxymethyl cellulose, and the mass ratio of the hard carbon, the carbon black, the styrene-butadiene rubber and the carboxymethyl cellulose is (9.0-9.5): (0.25-0.4): (0.125-0.3): (0.125-0.3);
[0025] And / or, the positive electrode conductive additive includes carbon black;
[0026] And / or, the positive electrode binder includes polyvinylidene fluoride.
[0027] Optionally, the sodium ion battery is a soft pack battery.
[0028] Optionally, the sodium titanate is dispersed on the surface of the hard carbon.
[0029] Considering that surface defects of hard carbon will affect battery performance, sodium titanate is dispersed on the surface of hard carbon to reduce the risk of reaction between hard carbon and electrolyte in direct contact, thereby reducing capacity attenuation problems related to surface defects of hard carbon.
[0030] Optionally, the negative electrode active material further includes phosphorus, and the mass percentage of the phosphorus is 0%-10% based on the total mass of the negative electrode active material.
[0031] In another embodiment of the present application, the negative electrode active material also includes phosphorus element, the mass percentage of phosphorus element is greater than 0% and less than 10%, phosphorus element has a higher capacity, and phosphorus element can be combined with sodium titanate and hard carbon to increase the overall capacity of the negative electrode.
[0032] Optionally, the hard carbon is provided on the surface of the phosphorus element.
[0033] Taking into account that the volume of phosphorus will expand during the sodium insertion process and that phosphorus has poor conductivity, hard carbon is dispersed on the surface of phosphorus to buffer the volume expansion of phosphorus, while enhancing the overall conductivity of the negative electrode active material and improving the cycle performance of the battery.
[0034] The sodium ion battery with improved energy density provided in the present application includes a positive electrode sheet and a negative electrode sheet, the positive electrode sheet includes a positive electrode current collector and a positive electrode coating provided on at least one side of the positive electrode current collector, the positive electrode coating includes a positive electrode active material, and the positive electrode active material includes a P2 phase material; the negative electrode sheet includes a negative electrode current collector and a negative electrode coating provided on at least one side of the negative electrode current collector, the negative electrode coating includes a negative electrode active material, and the negative electrode active material includes sodium titanate and hard carbon. The negative electrode active material of the present application includes sodium titanate and hard carbon, and the positive electrode active material includes a P2 phase material. The combination of the above-mentioned positive electrode active material and negative electrode active material helps to improve the energy density of the battery. DETAILED DESCRIPTION
[0035] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0036] "Scope" disclosed in the present application is limited in the form of lower limit and upper limit, and a given range is limited by selecting a lower limit and an upper limit, and the selected lower limit and upper limit define the boundary of a special range. The scope limited in this way can be including end values or not including end values, and can be arbitrarily combined, that is, any lower limit can be combined with any upper limit to form a scope. For example, if the scope of 60-120 and 80-110 is listed for a specific parameter, it is understood that the scope of 60-110 and 80-120 is also expected. In addition, if the minimum range values 1 and 2 are listed, and if the maximum range values 3, 4 and 5 are listed, the following scope can be all expected: 1-3, 1-4, 1-5, 2-3, 2-4 and 2-5. In the present application, unless otherwise specified, the numerical range "ab" represents the abbreviation of any real number combination between a and b, wherein a and b are real numbers. For example, the numerical range "0-5" means that all real numbers between "0-5" are listed in this document, and "0-5" is just an abbreviation of these numerical combinations. In addition, when a parameter is expressed as an integer ≥ 2, it is equivalent to disclosing that the parameter is, for example, an integer of 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.
[0037] Unless otherwise specified, all embodiments and optional embodiments of the present application can be combined with each other to form a new technical solution.
[0038] Unless otherwise specified, all technical features and optional technical features of this application can be combined with each other to form a new technical solution.
[0039] The sodium ion battery with improved energy density proposed in the present invention comprises a positive electrode plate and a negative electrode plate, the positive electrode plate comprises a positive electrode collector and a positive electrode coating arranged on at least one side of the positive electrode collector, the positive electrode coating comprises a positive electrode active material, and the positive electrode active material comprises a P2 phase material; the negative electrode plate comprises a negative electrode collector and a negative electrode coating arranged on at least one side of the negative electrode collector, the negative electrode coating comprises a negative electrode active material, and the negative electrode active material comprises sodium titanate and hard carbon.
[0040] The negative electrode active material of the present application includes sodium titanate and hard carbon, and the positive electrode active material includes a P2 phase material. The combination of the positive electrode active material and the negative electrode active material helps to improve the energy density of the battery.
[0041] It is understandable that sodium titanate (Na2TiO3) has good stability due to its simple crystal structure. Mixing sodium titanate with hard carbon can improve the cycle stability of the negative electrode and provide as a sodium source at the same time, thereby improving energy density. In addition, sodium titanate is simple to synthesize, the process is stable, and the material is relatively cheap. Considering that sodium titanate is used as a negative electrode, its sodium potential is high. By mixing sodium titanate with hard carbon, its sodium potential can be averaged. Moreover, the P2 phase material is used as the positive active material of the sodium ion battery. The combination of this positive and negative electrode system helps to improve the energy density of the battery. In addition, sodium titanate contains sodium ions, which can achieve the effect of supplementing sodium at the negative electrode. The positive and negative electrode system of this application can improve the energy density of the battery.
[0042] In one embodiment, the mass ratio of sodium titanate to hard carbon is (3-7):(7-3).
[0043] The mass ratio of sodium titanate to hard carbon satisfies the above range, which helps to improve the energy density of the battery and the cycle stability of the negative electrode.
[0044] In one embodiment, the P2 phase material includes sodium nickel manganese oxide and / or sodium nickel iron manganese oxide.
[0045] It is understandable that the potential of the positive and negative electrode materials has a direct impact on the energy density of the battery. The energy density of the battery can be estimated by the formula E = (Q × ΔU) / m, where E is the energy density of the battery, Q is the capacity of the battery, ΔU is the average voltage difference between the positive and negative electrodes, and m is the mass of the battery. From this formula, it can be seen that increasing the battery operating voltage (ΔU) can effectively increase the energy density of the battery.
[0046] The layered oxide positive electrode active material of the P2 phase generally exhibits a higher operating voltage and good electrochemical performance, and the negative electrode active material includes a mixture of sodium titanate and hard carbon, which can improve the stability of the negative electrode while reducing the operating voltage of the negative electrode. The use of the positive and negative electrode system of the present application helps to increase the battery operating voltage (ΔU), thereby helping to increase the energy density of the battery.
[0047] For example, in one embodiment, the P2 phase material includes sodium nickel manganese oxide Na 0.72 Ni 0.28 Mn 0.72 O2, in which the molar ratio of sodium (Na) is less than 1, and it is a sodium-deficient material. The negative electrode active material includes sodium titanate, which helps to supplement the sodium on the positive electrode side.
[0048] In one embodiment, the ratio of the negative electrode capacity to the positive electrode capacity of the sodium ion battery is 0.9 to 1.1, preferably 1:1.
[0049] Using the positive and negative electrode system of the present application, the ratio of the negative electrode capacity to the positive electrode capacity of the sodium ion battery is 0.9 to 1.1, preferably 1:1. The equal positive and negative electrode capacities help balance the redox reactions of the battery, thereby obtaining better charge and discharge performance and cycle stability. When the positive and negative electrode capacities are matched, the sodium storage capacity of the two-pole materials can be fully utilized to improve the energy density of the battery. Matching positive and negative electrode capacities helps reduce irreversible capacity losses during initial charging and improves the coulombic efficiency of the battery. Equal positive and negative electrode capacities can simplify the battery design and manufacturing process because there is no need to consider how to balance the capacities of the two poles. Balanced positive and negative electrode capacities help avoid overcharging or over-discharging due to capacity mismatch, thereby improving the safety of the battery.
[0050] In one embodiment, the positive electrode coating further includes a positive electrode conductor and a positive electrode binder, and the mass ratio of the positive electrode active material, the positive electrode conductor, and the positive electrode binder is (90-98): (2-8): (2-5).
[0051] In one embodiment, the negative electrode coating further includes a negative electrode conductive agent and a negative electrode binder, and the mass ratio of the negative electrode active material, the negative electrode conductive agent, and the negative electrode binder is (90-98): (5-8): (2-5).
[0052] In one embodiment, the compaction density of the negative electrode coating is 0.9 g / cm3 to 2.5 g / cm3.
[0053] In one embodiment, the mass energy density of the sodium ion battery is 90 wh / kg to 145 wh / kg.
[0054] The positive electrode coating also includes a positive electrode conductive agent and a positive electrode binder. The mass ratio of the positive electrode active material, the positive electrode conductive agent, and the positive electrode binder is (90-98): (2-8): (2-5). For example, the mass ratio of the positive electrode active material, the positive electrode conductive agent, and the positive electrode binder can be 95:2.5:2.5, etc. The mass ratio of the above components is within the above range, which can ensure the performance of the positive electrode. Among them, the positive electrode active material, the positive electrode conductive agent, and the positive electrode binder can all be the positive electrode active material, positive electrode conductive agent, and positive electrode binder known in the art for sodium ion batteries.
[0055] The negative electrode coating also includes a negative electrode conductive agent and a negative electrode binder. The mass ratio of the negative electrode active material, the negative electrode conductive agent, and the negative electrode binder is (90-98): (5-8): (2-5). The mass ratio of the above components is within the above range, which can ensure the performance of the negative electrode. The materials of the negative electrode coating and the materials of the positive electrode coating are used in combination to ensure the performance of the sodium ion battery; wherein the ratio of the negative electrode capacity to the positive electrode capacity of the sodium ion battery is 0.9 to 1.1, and the negative electrode of the sodium ion battery consumes a moderate amount of sodium ions of the positive electrode, which is beneficial to ensure the cycle performance and service life of the sodium ion battery.
[0056] The negative electrode active material of the present application includes sodium titanate and hard carbon. The use of the above negative electrode active material can improve the compaction density of the negative electrode coating, which is beneficial to improving the energy density of the battery.
[0057] The energy density of the sodium ion battery using the positive and negative electrode system of the present application is improved.
[0058] In one embodiment, the negative electrode coating further includes carbon black, styrene butadiene rubber and carboxymethyl cellulose, and the mass ratio of hard carbon, carbon black, styrene butadiene rubber and carboxymethyl cellulose is (9.0-9.5): (0.25-0.4): (0.125-0.3): (0.125-0.3).
[0059] In one embodiment, the positive electrode conductive additive includes carbon black.
[0060] In one embodiment, the positive electrode binder includes polyvinylidene fluoride.
[0061] In one embodiment, the sodium ion battery is a soft pack battery.
[0062] In one embodiment, sodium titanate is dispersed on the surface of hard carbon.
[0063] Considering that surface defects of hard carbon will affect battery performance, sodium titanate is dispersed on the surface of hard carbon to reduce the risk of reaction between hard carbon and electrolyte in direct contact, thereby reducing capacity attenuation problems related to surface defects of hard carbon.
[0064] In one embodiment, the negative electrode active material further includes phosphorus, and the mass percentage of the phosphorus is 0%-10% based on the total mass of the negative electrode active material.
[0065] In another embodiment of the present application, the negative electrode active material also includes phosphorus element, the mass percentage of phosphorus element is greater than 0% and less than 10%, phosphorus element has a higher capacity, and phosphorus element can be combined with sodium titanate and hard carbon to increase the overall capacity of the negative electrode.
[0066] In one embodiment, hard carbon is provided on the surface of the phosphorus element.
[0067] Taking into account that the volume of phosphorus will expand during the sodium insertion process and that phosphorus has poor conductivity, hard carbon is dispersed on the surface of phosphorus to buffer the volume expansion of phosphorus, while enhancing the overall conductivity of the negative electrode active material and improving the cycle performance of the battery.
[0068] It can also be understood that in order to reduce the impact of volume expansion on the negative electrode side on battery performance, the diaphragm is a compressible diaphragm, that is, the diaphragm is squeezed during the expansion of the negative electrode to relieve the stress of expansion on the negative electrode side. After the squeezing force is withdrawn, the diaphragm will expand and recover. It can be understood that at 2.5Mpa, the thickness of the diaphragm before extrusion is t1, and the thickness after extrusion is t2. The compression rate of the diaphragm is (t1-t2) / t1×100%, and the range of the diaphragm compression rate is 5% to 20%.
[0069] Taking into account that the pores of the diaphragm will be compressed and become smaller during the extrusion process, which is not conducive to the transmission of positive and negative electrode materials, for this reason, the diaphragm includes adjacent first and second film layers. The first film layer is difficult to be compressed, and the second film layer is easy to be compressed. The porosity of the first film layer is smaller than that of the second film layer, and the second film layer has a larger porosity, so that the second film layer can maintain a certain porosity after being compressed, which is conducive to the passage of positive and negative electrode materials through the diaphragm.
[0070] For example, in one embodiment, the first film layer is a ceramic film, and the second film layer is an organic film layer. The ceramic film has good mechanical strength and is difficult to be compressed, while the organic film layer is easily compressed.
[0071] Furthermore, in order to prevent the organic film layer from being over-compressed and covering the surface of the ceramic membrane and covering the pores of the ceramic membrane, the organic film layer includes a plurality of strip membranes, and the plurality of strip membranes are spaced apart on the surface of the ceramic membrane, that is, there are gaps between adjacent strip membranes, so that at least part of the surface of the ceramic membrane is exposed, providing a smooth path for the transport of substances between the positive and negative electrodes.
[0072] In addition, due to its high temperature resistance, the ceramic membrane can improve the thermal stability of the battery and prevent the battery from thermal runaway when overheated, thereby improving the safety of the battery. The ceramic membrane can improve the wettability of the diaphragm to the electrolyte, thereby improving the ion conductivity and charge and discharge performance of the battery. The ceramic membrane can improve the mechanical strength of the diaphragm and prevent damage during battery assembly and use. The ceramic membrane has good chemical stability and is not easy to react with the electrolyte, which helps to extend the service life of the battery.
[0073] In one embodiment, the preparation method of the positive and negative electrode system of the sodium ion battery of the present application is: 0.72 Ni 0.28 Mn 0.72 O2) is mixed with a conductive agent and a binder in a solvent NMP, then coated and rolled to prepare a pole piece. The negative electrode sodium titanate (Na2TiO3) and hard carbon are mixed, then mixed with a conductive agent and a binder, then coated and rolled to prepare a sheet. The positive and negative electrodes are matched to prepare a soft-pack battery.
[0074] Example
[0075] Example 1
[0076] Positive electrode sheet: The positive electrode coating in the positive electrode sheet includes the positive electrode active material Na 0.72 Ni 0.28 Mn 0.72 O2, positive electrode conductive additive carbon black, positive electrode binder polyvinylidene fluoride, the mass ratio of each component is 95:2.5:2.5.
[0077] Negative electrode plate: The negative electrode coating in the negative electrode plate includes negative electrode active materials hard carbon and sodium titanate (mass ratio is 1:1), wherein the mass ratio of hard carbon, carbon black, styrene-butadiene rubber and carboxymethyl cellulose can be 9.0:0.25:0.125:0.125.
[0078] Preparation of batteries
[0079] The negative electrode sheet, the positive electrode sheet, the separator and the electrolyte are assembled into a battery and its performance is tested. It can be understood that the preparation of the positive electrode sheet, the negative electrode sheet, the separator and the electrolyte, and the assembly of the battery can be prepared according to the methods disclosed in the literature.
[0080] Example 2
[0081] Based on Example 1, the ratio of sodium titanate to hard carbon is 3:7.
[0082] Example 3
[0083] Based on Example 1, the ratio of sodium titanate to hard carbon is 7:3.
[0084] Comparative Example 1
[0085] On the basis of Example 1, all the negative electrode active materials are hard carbon.
[0086] Table 1 Experimental data list
[0087]
[0088] It can be seen from Table 1 above that by adopting the negative electrode active material system of the present application, the energy density of the battery is improved.
[0089] The above description is only an exemplary embodiment of the present invention, and does not limit the patent scope of the present invention. All equivalent structural changes made by using the present invention specification under the technical concept of the present invention, or directly / indirectly applied in other related technical fields are included in the patent protection scope of the present invention.
Claims
1. A sodium ion battery with improved energy density, characterized in that: It comprises a positive electrode sheet and a negative electrode sheet, wherein the positive electrode sheet comprises a positive electrode current collector and a positive electrode coating disposed on at least one side of the positive electrode current collector, wherein the positive electrode coating comprises a positive electrode active material, and the positive electrode active material comprises a P2 phase material; The negative electrode sheet includes a negative electrode current collector and a negative electrode coating disposed on at least one side of the negative electrode current collector. The negative electrode coating includes a negative electrode active material. The negative electrode active material includes sodium titanate and hard carbon.
2. The sodium ion battery with improved energy density according to claim 1, characterized in that: The mass ratio of the sodium titanate to the hard carbon is (3-7): (7-3).
3. The sodium ion battery with improved energy density according to claim 1 or 2, characterized in that: The P2 phase material includes sodium nickel manganate and / or sodium nickel iron manganate.
4. The sodium ion battery with improved energy density according to claim 1 or 2, characterized in that: The ratio of the negative electrode capacity to the positive electrode capacity of the sodium ion battery is 0.9 to 1.1, preferably 1:
1.
5. The sodium ion battery with improved energy density according to claim 1 or 2, characterized in that: The positive electrode coating further comprises a positive electrode conductive agent and a positive electrode binder, wherein the mass ratio of the positive electrode active material, the positive electrode conductive agent and the positive electrode binder is (90-98): (2-8): (2-5); And / or, the negative electrode coating further comprises a negative electrode conductive agent and a negative electrode binder, and the mass ratio of the negative electrode active material, the negative electrode conductive agent, and the negative electrode binder is (90-98): (5-8): (2-5); and / or, the compaction density of the negative electrode coating is 0.95 g / cm3 to 2.4 g / cm3; And / or, the mass energy density of the sodium ion battery is 90wh / kg to 145wh / kg.
6. The sodium ion battery with improved energy density according to claim 5, characterized in that: The negative electrode coating further comprises carbon black, styrene-butadiene rubber and carboxymethyl cellulose, wherein the mass ratio of the hard carbon, the carbon black, the styrene-butadiene rubber and the carboxymethyl cellulose is (9.0-9.5): (0.25-0.4): (0.125-0.3): (0.125-0.3); And / or, the positive electrode conductive additive includes carbon black; And / or, the positive electrode binder includes polyvinylidene fluoride.
7. The sodium ion battery with improved energy density according to claim 1 or 2, characterized in that: The sodium ion battery is a soft pack battery.
8. The sodium ion battery with improved energy density according to claim 1 or 2, characterized in that: The sodium titanate is dispersed on the surface of the hard carbon.
9. The sodium ion battery with improved energy density according to claim 1 or 2, characterized in that: The negative electrode active material further includes phosphorus, and the mass percentage of the phosphorus is 0%-10% based on the total mass of the negative electrode active material.
10. The sodium ion battery with improved energy density according to claim 9, characterized in that: The hard carbon is provided on the surface of the phosphorus element.